2006
DOI: 10.1002/adma.200500786
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Dots in Biological and Biomedical Research: Recent Progress and Present Challenges

Abstract: The marriage of nanomaterials with biology has produced a new generation of technologies that can profoundly impact biological and biomedical research. Quantum dots (Qdots) are an archetype for this hybrid research area and have gained popularity and interest from diverse research communities because of their unique and tunable optical properties. In this Review, we will describe their history and development, optical and electronic properties, and applications in biology and medicine. A critical evaluation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
415
0
4

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 598 publications
(420 citation statements)
references
References 131 publications
(121 reference statements)
1
415
0
4
Order By: Relevance
“…These results again suggest that a higher concentration of antibodies are immobilised on CNTs using a covalent modification approach. Quantum dots have previously been used as fluorescence labels for biomolecules [18]. This approach should be widely applicable to biomolecules immobilised on CNTs since it was determined that there was no interference in the fluorescence emissions (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…These results again suggest that a higher concentration of antibodies are immobilised on CNTs using a covalent modification approach. Quantum dots have previously been used as fluorescence labels for biomolecules [18]. This approach should be widely applicable to biomolecules immobilised on CNTs since it was determined that there was no interference in the fluorescence emissions (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…General reviews about the application of nanoparticles in biological systems can be found in a number of articles (Riu et al 2006;De et al 2008) focusing on analytics (Rosi & Mirkin 2005;Wilson 2008), gold nanoparticles (Jennings & Strouse 2007;Sperling et al 2008;Boisselier & Astruc 2009) and quantum dots (Hotz 2005;Medintz et al 2005;Michalet et al 2005;Klostranec & Chan 2006;Yu et al 2006a;Delehanty et al 2009;). Both surface modification and applications of magnetic iron oxide nanoparticles have been reviewed recently (Mosqueira et al 2001;Berry & Curtis 2003;Ueno & Sekino 2006;Lu et al 2007;Xu & Sun 2007;Laurent et al 2008;Sun et al 2008).…”
Section: Applications Outlookmentioning
confidence: 99%
“…Recently, colloidal spherical quantum dots have also proven to offer high performance in biological and medical applications. 7 A specific characteristic of biological and, in general, organic environments is their huge dielectric mismatch with typical inorganic semiconductor QD structures. When QDs are embedded in such environments, the formation of polarization charges at the interface may strongly influence confinement and modify the distribution of charge carriers inside the QD.…”
Section: Introductionmentioning
confidence: 99%